"Can you keep it real?" : Practical, and culturally tailored lifestyle recommendations by Mexican American women diagnosed with type 2 diabetes: A qualitative study - Sandra Benavides-Vaello; Sharon A. Brown; Roxanne Vandermause (BMC, 2017)
Abstract Background The purpose of this article is to engage clinicians in a dialogue about ideas on how to provide more specific, contextually relevant, practical and culturally tailored diabetes self-management recommendations as suggested by Mexican-American women diagnosed with type 2 diabetes. Current diabetes self-management recommendations, targeting Mexican Americans in particular, remain largely broad ("reduce your calorie intake" or "cut back on carbs"), overly ambitious ("stop eating tortillas"), and relatively ineffective (Svedbo Engström et al., BMJ Open 6(3):e010249, 2016; Johansson et al., Int J Qual Stud Health Well-being 11, 2016; Oomen et al., The Diabetes Educ 25:220-225, 1999; Franek, Ont Health Technol Assess Ser 13(9):1-60, 2013; Purnell et al. Patient 9:349, 2016). Methods A secondary and focused analysis (N = 12) was performed on data gathered from a larger qualitative study (N = 16), which explored diabetes among Mexican-American women residing in rural South Texas. Results Findings from the secondary analysis were that study informants elicited more realistic or contextually relevant, specific self-management strategies that reflected the cognitive, emotive, and behavioral areas but were reframed within the context of the Mexican-American culture. Self-management strategies fell into the categories of: (a) environmental controls, (b) avoiding overeating, (c) lifestyle changes, (d) cooking tips, and (e) active self-management. Conclusions Diabetes remains a serious health threat to Mexican Americans, women in particular. Few individuals attain glycemic control, likely due in part to the disconnect between global and non-contextual self-management recommendations offered by health care providers and the need for more detailed and realistic guidance required for the day-to-day self-management of diabetes.